Física dos anos iniciais: estudo sobre a queda livre dos corpos através da metodologia da mediação dialética - Silveira Junior, Pedro Belchior Da; Arnoni, Maria Eliza Brefere [UNESP] (Sociedade Brasileira de Física, 2013)
The model used in Brazilian schools, based on both traditional and progressive education, transmits information without worrying to show the real meaning of things, and without taking into consideration the previous knowledge of the pupil. How to work with the contents of human knowledge in a meaningful way? One alternative way is the Methodology of Dialectical Mediation (MDM), which consists in four steps or pedagogical moments, rescuing, problem posing, systematizing and producing. This theoretical option considers the educational work as a relationship involving teaching, learning and contents, which are taken as independent moments tightly connected to the ongoing work, instead of isolated elements or static terms. The aim of the present work is to clarify the Methodology of Dialectical Mediation and develop a class proposal according to the MDM approach to the problem of the free falling bodies (gravity, material means and shape). To evaluate the methodology, questionnaires were applied after experiments, with the involvement of students at each predominant moment. The results suggested that the MMD, combined with experimental activity, is a tool that enhances the overcoming of immediate knowledge, allowing students to reach a better understanding of the scientific knowledge.

O modelo usado nas escolas brasileiras, baseado nos tipos de educação tradicional e progressiva, transmite as informações sem a preocupação de mostrar o significado real dos fatos, não levando em conta o conhecimento da criança. Mas, como trabalhar os conteúdos do conhecimento humano de maneira significativa? Uma das alternativas seria a Metodologia da Mediação Dialética (MMD), composta por quatro etapas ou momentos pedagógicos: resgatando, problematizando, sistematizando e produzindo. Essa opção teórica entende o trabalho educativo como uma relação processual entre ensino, aprendizagem e conteúdo, considerando-os como momentos independentes e indissoluvelmente vinculados desse trabalho, e não como elementos isolados ou termos estáticos. Assim, o objetivo do trabalho foi esclarecer a Metodologia da Mediação Dialética e desenvolver uma proposta de aula segundo a MMD focando-se na temática da queda livre dos corpos (força gravitacional, meio material e forma dos corpos). Para avaliar a metodologia, foram aplicados questionários após os experimentos visando obter o envolvimento dos alunos em cada um dos momentos predominantes. Os resultados demonstraram que a MMD (aliada à atividade experimental) é um instrumento que potencializa a superação do saber imediato, via contradições, permitindo ao aluno compreender o saber científico.
The physics of early years: study of free falling bodies by the methodology of dialectical mediation
Keywords: physics education; methodology of dialectical mediation; Física; Educação; metodologia da mediação dialética